Pancasila Democracy: Non-Systemic Legal Studies Charles Sampford - Triwahyuningsih (LEGAL BRIEF, 2021)
The ethical orientation of the ideals of Pancasila democratic law as desired by the founding fathers is contained in the Preamble of the 1945 Constitution of the Republic of Indonesia paragraph IV, a structure of the Republic of Indonesia is formed which is sovereignty of the people based on the state philosophy, namely the values of "divinity , humanity, unity, deliberation and justice ”, have not been fully implemented. The purpose of this research is to analyze Pancasila democracy concept when viewed from non-systemic law Charles Sampford.This study uses a philosophical normative approach combined with a qualitative descriptive analysis. The results show that the concept of non-systemic legal science provides an alternative to different reading models of Pancasila as a complete and holistic system, both in terms of meaning and relations. The characteristic of deliberation in Pancasila Democracy is that differences are basically aimed at finding equality, descriptively, that deliberation is allowed to remain in differences, because in essence there are differences.